Molecular genetics of pulmonary arterial hypertension - Trembath, Richard C. (Henry Stewart Talks, 2014)
Histopathology of PAH, Familial PAH: classical linkage, Variable age of onset and penetrance, Pathogenesis of HHT & PAH, Key genes in the pathogenesis of PAH, The BMPR2 mutation (classification as iPAH), Different kinds of genetic factors for PAH, A locus for susceptibility to PAH, Exome sequencing for disease causing variants, Mutation locations in KCNK3, Variants identified in familial and idiopathic PAH, Potential role of gene mutations in PAH, Genetic counselling for PAH, Asymptomatic relatives and families without mutation, Aim of latest research in UK